2009
DOI: 10.2217/bmm.09.7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Type 1 Diabetes: Immune Response Genes

Abstract: Type 1 diabetes (T1D) is a polygenic autoimmune disease. Susceptibility to T1D is strongly linked to a major genetic locus that is the MHC, and several other minor loci including insulin, cytotoxic T-lymphocyte-associated antigen-4, PTPN22 and others that contribute to diabetes risk in an epistatic way. We have observed that there are three sets of DR3-positive autoimmunity-favoring haplotypes in the north-Indian population, including B50-DR3, B58-DR3 and B8-DR3. The classical Caucasian autoimmunity favoring A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 192 publications
(197 reference statements)
1
3
0
Order By: Relevance
“…An analogy can be speculated in the Indian population where B8 -DR3 haplotypes are comparatively less predisposing to T1D than the B50 -DR3 and B58 -DR3 haplotypes, whereas B18 -DR3 is rare. This is based on the observation that B8 -DR3 carries a relative risk of 4.4, whereas B50 -DR3 and B58 -DR3 have stronger relative risks of 9.4 and 7.3, respectively [22]. In the present study, the 3-locus TNF haplotypes (TNF-␣ Ϫ238,TNF-␣ Ϫ308, and TNFa) were observed to be variably associated with the 3 sets of HLA-DR3 ϩ haplotypes.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…An analogy can be speculated in the Indian population where B8 -DR3 haplotypes are comparatively less predisposing to T1D than the B50 -DR3 and B58 -DR3 haplotypes, whereas B18 -DR3 is rare. This is based on the observation that B8 -DR3 carries a relative risk of 4.4, whereas B50 -DR3 and B58 -DR3 have stronger relative risks of 9.4 and 7.3, respectively [22]. In the present study, the 3-locus TNF haplotypes (TNF-␣ Ϫ238,TNF-␣ Ϫ308, and TNFa) were observed to be variably associated with the 3 sets of HLA-DR3 ϩ haplotypes.…”
Section: Discussionsupporting
confidence: 47%
“…Further, 3 groups of HLA-DR3 ϩ haplotypes have been identified as being associated with type 1 diabetes in this population compared with mainly AH8.1 (HLA-A1-B8 -DR3) or the B18 -DR3 haplotypes in Caucasians [19,20]. These haplotypes include HLA-B8 -DR3 (ancestral haplotype AH8.2 and others) [22], HLA-B50 -DR3 (AH50.2), and HLA-B58 -DR3 (AH58.1). The AH58.1 haplotype confers a similar level of risk for development of T1D as it does among the Chinese [24,25], whereas the association of the AH50.2 haplotype is "unique" to the Indian population.…”
Section: Introductionmentioning
confidence: 95%
“…In the North Indian population, on the other hand, the greatest risk is conferred by the DR3‐DQ2 haplotypes with almost no association with DR4‐DQ8, both in T1D as well as active CD . Multiple HLA‐DR3‐DQ2 haplotypes have been encountered and found to be associated with the two diseases in the Indian population which is quite in contrast to the situation in Caucasians .…”
Section: A Comparison Of Age and Sex Distribution Among Healthy Contrmentioning
confidence: 93%
“…In the Caucasian populations, two high-risk haplotypes, namely HLA-DRB1*04-DQA1*03:01-DQ B1*03:02 and HLA-DRB1*03-DQA1*05:01-DQB1* 02:01 and a protection conferring haplotype (HLA-DRB1*15-DQA1*01:02/03-DQB1*06:01/02) have been identified (Ronningen et al, 1991;Sanjeevi et al, 1995;Lambert et al, 2004). In the North Indian population, on the other hand, multiple DR3-DQ2 (DRB1*03:01-DQA1*05:01-DQB1*02:01) haplotypes confer susceptibility to the disease, while the HLA-DR4-DQ8 remains neutral (Mehra et al, 2002(Mehra et al, , 2007Kanga et al, 2004;Kumar et al, 2009Kumar et al, , 2013. IDDM2 refers to the insulin gene (INS) locus on chromosome 11p15.5 that contains variable number tandem repeats (VNTR) upstream of the insulin gene.…”
Section: Introductionmentioning
confidence: 99%